Toxicity of gabapentin-lactam on the early developmental stage of zebrafish (Danio rerio). (15th October 2021) - He, Yide; Jia, Dantong; Du, Sen; Zhu, Rongwen; Zhou, Wei; Pan, Shunlong; Zhang, Yongjun
Abstract: Gabapentin-lactam (GBP-L) is a transformation product (TP) of gabapentin (GBP), a widely used anti-epileptic pharmaceutical. Due to its high persistence, GBP-L has been frequently detected in the surface water. However, the effects of GBP-L on aquatic organisms have not been thoroughly investigated. In the present study, zebrafish ( Danio rerio ) embryos as a model organism were used to study the impacts of GBP-L in terms of embryos LC50, spontaneous movement at 24 hpf (hours post fertilization), heartbeat rates at 48 hpf, and body length at 72 hpf, with the concentrations of GBP-L down to 0.01 μg/L, covering its environmental concentrations. Various biomarkers from nervous, antioxidant and immune systems of zebrafish larvae were analyzed, including acetylcholinesterase, acetylcholine, dopamine, gamma-aminobutyric acid, superoxide dismutase, catalase, glutathione S-transferase, C reactive protein, and lysozyme, to assess its toxicity on these systems. RT-qPCR was then used to further verify the results and explain the toxicological mechanism at the gene level. The results demonstrated that GBP-L is much more toxic than its parent compound, and could lead to adverse impacts on the aquatic organisms even at every low concentrations. Graphical abstract: Image 1 Highlights: GBP-L could induce higher acute toxicity than its parent compound GBP. GBP-L could induce developmental toxicity to zebrafish embryos. GBP-L of environmental concentration could adversely affect the nervous system. GBP-L of environmental concentration could adversely affect antioxidant system. GBP could interfere with immune system. Abstract : The toxicity of GBP-L, a TP of GBP, was evaluated, showing that it can exert adverse effects on the early development of zebrafish at environmental concentration.